Surgery - Martínez, José Luis; Sanjines, Aníbal (Cirugía del Uruguay, 1974)
We have carried out the surgical therapeutic approach to tumors of the mediastinum (T.M.) based on the joint experience of the surgeons who work at the Institute of Thorax Diseases (Colonia Gustavo Saint Bois).